Combined thermal and FTIR analysis of porous silicon based nano-energetic films. Issue 12 (23rd January 2017) - Plummer, A.; Kuznetsov, V. A.; Gascooke, J. R.; Shapter, J.; Voelcker, N. H.
Abstract : Combinations of analytical techniques lead to new insights for the early stages of explosive reactions. Abstract : Nanoporous silicon (pSi) films on a silicon wafer were loaded with sodium perchlorate (SP) and perfluoropolyether (PFPE) oxidising agents to generate a pyrotechnic energetic material. The potentially violent reaction between the silicon and the loaded oxidising agent was studied using correlated differential scanning calorimetry (DSC) and FTIR spectroscopy for samples heated continuously between ambient and 500 °C. We observed that the energetic reaction between pSi and SP depended on the presence of various hydride species on the surface of freshly etched pSi, and on formation of volatile free radical species released during either oxidation of the surface in the presence of air at about 200 °C or during desorption of the hydride above 270 °C in the absence of oxygen. However, energetic reactions between pSi and PFPE were delayed until pyrolysis of the PFPE above 390 °C in the absence of oxygen, suggesting PFPE's suitability for pyrotechnics applications. Correlated thermal and spectroscopic methods of analysis gave new insights into the earliest stages of the reaction of these energetic materials.